Strategi Integrated Marketing Communication Pada Agensi Timor Creative People - Maharani, Ni Ayu Laura; Teguh, Monika (Jurnal Pustaka Komunikasi, 2025)
The entertainment industry has grown rapidly, including in small cities such as Kupang. This provides opportunities for the younger generation to channel their talents and abilities. Timor Creative People Agency plays a role in developing creativity and talent in the entertainment sector. Success in marketing an entertainment agency requires attention to its marketing communication strategies to ensure its services can be used to complete outstanding projects. This research aims to understand the implementation of integrated marketing communication strategies used by Timor Creative People Agency to attract interest in the entertainment world, particularly in modeling. This study uses a qualitative method with data collection techniques including semi-structured interviews and documentation. The data analysis used in this study follows three stages: data reduction, presentation, and verification. Data validation is carried out using source triangulation by comparing data from various informant categories. The results of this study indicate that Timor Creative People Agency has implemented integrated marketing communication strategies including advertising, direct marketing, public relations, word of mouth, events experiences, personal selling, and digital marketing. The key activities in boosting the marketing of Timor Creative People Agency are digital marketing and personal selling.